Analisis Dampak Penggunaan Tiktok Terhadap Perilaku Sopan Santun Peserta Didik Sekolah Dasar - Satya Hafifah; Lusi Herlina Fitri; Ismy Nurfadila; Malika Rahmadani Siregar; Indah Aulia Putri (Jurnal Bintang Pendidikan Indonesia, 2025)
This study aims to analyze the impact of TikTok usage on the politeness behavior of elementary school students. Using the Systematic Literature Review (SLR) method, this article examines various previous studies related to the topic. The findings indicate that TikTok usage has a significant influence on students' behavior, particularly in terms of politeness. Although there are some positive effects, such as enhanced creativity, self-confidence, and cognitive abilities, the negative impacts are more dominant. Students tend to show a decline in polite behavior, such as the use of harsh language, lack of respect for parents and teachers, and reduced responsibility towards school assignments. High intensity of TikTok usage is one of the main factors contributing to the development of such deviant behavior. Therefore, the role of teachers and parents is crucial in supervising, setting examples, and guiding students to use social media wisely in order to uphold character and moral values.